CHF6001 Inhibits NF-κB Activation and Neutrophilic Recruitment in LPS-Induced Lung Inflammation in Mice - Stellari, Fabio F.; Sala, Angelo; Ruscitti, Francesca; Buccellati, Carola; Allen, Andrew; Risé, Patrizia; Civelli, Maurizio; Villetti, Gino (Frontiers in Pharmacology, 2019)
Inhibitors of phosphodiesterase 4 (PDE4) are potent anti-inflammatory agents, inhibiting the production of inflammatory mediators through the elevation of intracellular cAMP concentrations. We studied the activity of a novel PDE4 inhibitor, CHF6001 both in vitro in human cells and in vivo, using bioluminescence imaging (BLI) in mice lung inflammation. Mice transiently transfected with the luciferase gene under the control of an NF-κB responsive element (NF-κB-luc) have been used to assess the in vivo anti-inflammatory activity of CHF6001, in lipopolysaccharide (LPS)-induced lung inflammation. BLI as well as inflammatory cells and concentrations of proinflammatory cytokines, were monitored in bronchoalveolar lavage fluids (BALF) while testing in vitro its ability to affect the production of leukotriene B4 (LTB4), measured by LC/MS/MS, by LPS/LPS/fMLP-activated human blood. CHF6001 inhibited the production of LTB4 in LPS/fMLP activated human blood at sub-nanomolar concentrations. LPS-induced an increase of BLI signal in NF-κB-luc mice, and CHF6001 administered by dry powder inhalation decreased in parallel luciferase signal, cell airways infiltration and proinflammatory cytokines concentrations in BALF. The results obtained provide in vitro and in vivo evidence of the anti-inflammatory activity of the potent PDE4 inhibitor CHF6001, showing that with a topical administration that closely mimics inhalation in humans, it efficiently disrupts the NF-κB activation associated with LPS challenge, an effect that may be relevant for the prevention of exacerbation episodes in COPD subjects.